Challenges of rehabilitation for patients with primary malignant glioma – a review of recent literature - Hojan, Katarzyna (Journal of Medical Science, 2016)
Primary malignant glioma is one of the greatest challenges in contemporary rehabilitation. Due to the introduction of newer and newer methods of oncological treatment the overall survival in this group of patients retrospectively increased. This article is a review of the scientific literature of recent years concerning the principles of clinical assessment of patients with primary glioblastoma and the selection of methods in rehabilitation programs based on general condition. In the last years, there has been an increase in the results of clinical studies on the implementation of rehabilitation treatment in primary malignant glioma patients after oncological treatment. Thus, identification of accurate functional performance, behavior changes, evaluation of cognitive function, and cancer markers and oncological treatment as well as quality of life outcomes in this population are of major clinical importance. Primary malignant glioma patients represent a unique patient population with distinctive functional impairments and limitations to physical exercise. Therefore, individual comprehensive rehabilitation treatment may be useful in improving the physical and cognitive functioning as well as decreasing the fatigue syndrome. Such a therapy allows this group of patients to participate in society despite the consequences of cancer treatment.
Keywords: brain tumor; exercise; oncology